Biodegradable soy protein films with controllable water solubility and enhanced mechanical properties via graft polymerization. (November 2016) - Zhao, Yi; Xu, Helan; Mu, Bingnan; Xu, Lan; Yang, Yiqi
Abstract: Graft polymerization of acrylic acid endowed soy protein films with good tensile properties and water solubility without sacrificing biodegradability. In this research, soy protein was grafted with acrylic acid and cast into biodegradable films as substitutes of non-biodegradable Poly(vinyl alcohol) (PVA) films. The grafted soy protein films had 318%, 114%, 60% and 9% higher tensile strength, elongation, dissolving rate and transmittance, compared to ungrafted ones, respectively. Acrylic acid grafting provided soy protein films with biodegradability, flexibility, and adhesion to yarns substantially higher than PVA, while water solubility and abrasion resistance similar to PVA, leading to high potential applications of the grafted soy proteins in the fields of water soluble packaging films and slashing to substitute PVA. Highlights: Biodegradable film was made from acrylic acid grafted soy protein for the first time. Acrylic acid grafting rendered soy protein film water soluble controllably. Acrylic acid grafting remarkably improved tensile properties of soy protein film. Acrylic acid grafting could promote use of proteins as fast-dissolving packaging films and protective coating of yarns.